Clinical validation of the Virtual Reality Functional Capacity Assessment Test – Short List (VRFCAT‐SLx) for assessment of iADL functioning in early symptomatic dementia: Baseline performance and associations with standard measures. (20th December 2022) - Atkins, Alexandra S; Schoemaker, Dorothee; Abraham, Chelsea; Flanagan, Chloe; Evans, Haley; Madsen, Corrine; Sickel, Nancy; Stevens, Heather; Amaya, Alexandra C; Plassman, Brenda L; Loewenstein, David; Welsh‐Bohmer, Kathleen A.; et al.
Abstract: Background: Clinical trials in preclinical and early symptomatic Alzheimer's disease require increased precision for the assessment and monitoring of functional capacity. The Virtual Reality Functional Capacity Assessment Tool (VRFCAT) is a performance‐based assessment of function with the potential to serve this need. Prior work has demonstrated the VRFCAT's validity and sensitivity as a measure of iADL functioning in subjective cognitive decline (Atkins et al., 2019), but pilot work in more cognitively impaired individuals indicated a risk of floor effects in some patients. The VRFCAT "Short List" (VRFCAT‐SLx) was developed to address this issue by modifying the test to reduce length and complexity. We present Baseline data from an ongoing clinical validation study of the VRFCAT‐SLx in participants with clinically characterized MCI/AD dementia Method: At the time of submission, participants included 77 adults (32 male; mean age = 73.29, SD = 7.52) with established diagnoses of MCI or mild AD (NIA‐AA criteria) and CDR global scores of 0.5 or 1.0. Participants completed the tablet‐based VRFCAT‐SLx and other established measures (ADCS‐ADL‐MCI, MMSE, CDR, BAC cognitive tests) at Baseline and Follow‐up. At submission, 22 participants had completed follow‐up. Statistical analyses of baseline data, reported here, examined VRFCAT‐SLx task completion rates, the frequency of "floor" level performance, and baseline correlations with standard measures. Result: Mean MMSE at Baseline was 27.47 (SD = 2.0). Cognitive performance reflected diagnoses of MCI, with the greatest impairments on verbal memory (1‐1.5 SD below the normative mean). All participants were able to complete the VRFCAT‐SLx at Baseline; 97.4% of participants (all but 2) met a priori set criteria for performance validity. VRFCAT‐SLx completion time (Total Adjusted Time) was significantly correlated with partner‐reported functioning on the ADCS‐ADL‐MCI (r = ‐.48, p<.001), the CDR‐SB (r = .37, p<.001), and BAC cognitive measures including Verbal List Learning (r = ‐.42, p<.001), Delayed Recall (r = ‐.40, p<.001), Tower of London (r = ‐.45, p<.001), and Symbol Coding (r = ‐.42, p<.001). Conclusion: Baseline results support the use of the VRFCAT‐SLx as a performance‐based assessment of functioning in early symptomatic MCI/AD. Strong associations between VRFCAT‐SLx scores, partner‐reported functioning, clinical staging, and cognition replicate and extend earlier findings regarding the construct validity and clinical relevance of the tool.